PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN E-LKPD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATERI TRANSFORMASI GEOMETRI PADA SISWA KELAS IX SMP NEGERI 4 PRAYA TAHUN AJARAN 2025/2026 - Sephiyana, Baiq Dita; Prayitno, Sudi; Nilza Humaira Salsabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by students’ low problem-solving skills, which stem from the use of ineffective conventional teaching models and the limited use of instructional media. This study aims to examine the effect of the Problem-Based Learning (PBL) model supported by E-LKPD on the geometric transformation problem-solving skills of 9th-grade students at SMP Negeri 4 Praya during the 2025/2026 academic year. This study employs a quasi-experimental design with a quantitative approach and a posttest-only control group. The research sample was selected using purposive sampling, with Class IX-1 serving as the experimental class receiving the PBL model supported by E-LKPD, and Class IX-2 serving as the control class using the direct instruction model. The results of this study indicate that the average posttest score of the experimental class (85.95) was higher than that of the control class (76.65). Based on a t-test calculation using SPSS with a 5% significance level, the sig. value (two-tailed) was 1.68023, which is less than 0.05, indicating a significant difference between the two groups. In addition, the effect size test result showed a value of 0.722, which falls into the moderate category, indicating that the PBL model supported by E-LKPD has a positive impact on students’ problem-solving skills.